The Columbia documentary history of religion in America since 1945 - Harvey, Paul, 1961-; Goff, Philip, 1964- (Columbia University Press, 2005)
Of late, religion seems to be everywhere, suffusing U.S. politics and popular culture and acting as both a unifying and divisive force. This collection of manifestos, Supreme Court decisions, congressional testimonies, speeches, articles, book excerpts, pastoral letters, interviews, song lyrics, memoirs, and poems reflects the vitality, diversity, and changing nature of religious belief and practice in American public and private life over the last half century. Encompassing a range of perspectives, this book illustrates the ways in which individuals from all along the religious and political spectrum have engaged religion and viewed it as a crucial aspect of society.